2021
DOI: 10.3389/fgene.2021.614379
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Modified Rabbits for Cardiovascular Research

Abstract: Rabbits are one of the most used experimental animals for investigating the mechanisms of human cardiovascular disease and lipid metabolism because they are phylogenetically closer to human than rodents (mice and rats). Cholesterol-fed wild-type rabbits were first used to study human atherosclerosis more than 100 years ago and are still playing an important role in cardiovascular research. Furthermore, transgenic rabbits generated by pronuclear microinjection provided another means to investigate many gene fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 147 publications
(131 reference statements)
2
11
0
4
Order By: Relevance
“…Forty rabbits were successfully delivered. Sixteen rhPA/gGH double transgenic rabbits (10♂,6♀) were obtained by PCR integration detection, and the double gene integration rate reached 40.0%, which was consistent with the integration efficiency of transgenic rabbits reported at home and abroad [16,[38][39][40][41] . The mammary gland expression levels of the six rhPA/gGH double transgenic female rabbits showed that rhPA expressed level in whey were about 4.98-12.24g/L, which were much higher than those of rhPA single transgenic rabbits (0.27-0.63 g/L), and increased by about 17.2-23.8 times.…”
Section: Discussionsupporting
confidence: 79%
“…Forty rabbits were successfully delivered. Sixteen rhPA/gGH double transgenic rabbits (10♂,6♀) were obtained by PCR integration detection, and the double gene integration rate reached 40.0%, which was consistent with the integration efficiency of transgenic rabbits reported at home and abroad [16,[38][39][40][41] . The mammary gland expression levels of the six rhPA/gGH double transgenic female rabbits showed that rhPA expressed level in whey were about 4.98-12.24g/L, which were much higher than those of rhPA single transgenic rabbits (0.27-0.63 g/L), and increased by about 17.2-23.8 times.…”
Section: Discussionsupporting
confidence: 79%
“…Due to their short life spans, short gestation period, high number of progeny, relatively low cost (compared with other large animals such as dogs, pigs and monkeys), and availability of genomics and proteomics, 56 rabbits can bridge the gap between smaller rodents and larger animals, and play an important role in translational research such as pre-clinical testing of drugs and diagnostic methods for patients. 52,57,58 Lipoprotein metabolism features of rabbits are close to those of humans, as are the lesions of atherosclerosis, being advantages to examine lipoprotein metabolism and atherosclerosis (Table 1). We created both transgenic and KO rabbits to study apolipoproteins (apo), including apo(a), apoAII, apoB, apoCIII, apoE, enzymes (endothelial lipase, hepatic lipase and lipoprotein lipase) and cholesteryl ester transfer protein proteins (CETP) expressed in the liver.…”
Section: Animal Modelsmentioning
confidence: 99%
“…We created both transgenic and KO rabbits to study apolipoproteins (apo), including apo(a), apoAII, apoB, apoCIII, apoE, enzymes (endothelial lipase, hepatic lipase and lipoprotein lipase) and cholesteryl ester transfer protein proteins (CETP) expressed in the liver. 58 We also generated different rabbit models to examine the functional roles F I G U R E 6 Simplified schema of initial cellular events during the pathogenesis of atherosclerosis. Risk factors, such as hypercholesterolemia (yellow dots), may upregulate the adhesion molecules of endothelial cells (EC), which leads to the adherence of monocytes (Mon) and T lymphocytes (Lym) on the surface of intima (left).…”
Section: Animal Modelsmentioning
confidence: 99%
“…Interestingly, genetic ablation of CETP gene in the rabbit model demonstrated athero-protective effects, suggesting a potential therapeutic target for atherosclerosis treatment [146]. Meanwhile, the Watanabe heritable hyperlipidemic (WHHL) rabbits are often used as a human familial hypercholesterolemic model due to its characteristic high LDL levels [147]. Following the discovery of CRISPR/Cas9, knockout rabbit models are made possible with the capability to target different gene of interests [148].…”
Section: In Vivo Disease Modelingmentioning
confidence: 99%